2017
DOI: 10.1002/jrs.5086
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of the vibrational properties of bulk 2H–MoS2 and its exfoliated nanosheets under high pressure

Abstract: In this paper, we present a comparative study of the vibrational properties of bulk MoS2 and its exfoliated nanosheets under high pressure by resonant Raman spectroscopy. The X‐ray photoelectron spectroscopy measurements demonstrate that the nanosheets made by chemical lithium insertion method are mainly consisted of metallic 1T phase. The wavenumbers of the Ebold2boldg1 and Alg Raman modes for the few layer nanosheets show a linear relationship with pressure which is different from the multilayer MoS2. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The spectrum of 2H‐MoS 2 shows two main Raman‐active lattice vibrations at 386 (E 1 2g ) and 411 cm −1 (A 1g ), respectively. They are accompanied by the bands expected for resonant 633 nm excitation, including 180 (A 1g ‐LA(M)), 420 (B1u), 454 (2LA(M)), and 467 (A 2u ) cm −1 [36,37] . The presence of 1T‐MoS 2 in the layers of Phen‐MoS 2 is indicated by the appearance of additional modes J 1 , J 2 , and J 3 , typical of 1T‐MoS 2 modification [38,39] at 192, 229 and 289 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…The spectrum of 2H‐MoS 2 shows two main Raman‐active lattice vibrations at 386 (E 1 2g ) and 411 cm −1 (A 1g ), respectively. They are accompanied by the bands expected for resonant 633 nm excitation, including 180 (A 1g ‐LA(M)), 420 (B1u), 454 (2LA(M)), and 467 (A 2u ) cm −1 [36,37] . The presence of 1T‐MoS 2 in the layers of Phen‐MoS 2 is indicated by the appearance of additional modes J 1 , J 2 , and J 3 , typical of 1T‐MoS 2 modification [38,39] at 192, 229 and 289 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Molybdenum disulfide (MoS 2 ), one of the transition‐metal dichalcogenides with a layered structure, presents hexagonal (2H‐MoS 2 ) or rhombohedral (3R‐MoS 2 ) symmetry in nature (a third phase, 1T‐MoS 2 , is a metastable metallic material) . Both phases are semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al reported a comparative investigation of the vibrational properties of bulk 2H ‐MoS 2 and its exfoliated nanosheets under high pressure. The systematic research about the 2LA (M) in bulk 2H ‐MoS 2 suggests that the high‐pressure behavior of this double resonance Raman mode arises from the pressure‐induced metalization and band gap closure . Krylov et al presented a Raman study of HoFe 3 (BO 3 ) 4 at simultaneously high pressure and high temperature that yielded a P–T phase diagram.…”
Section: High Pressure and Temperature Studiesmentioning
confidence: 99%